ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN BERAU DENGAN PENDEKATAN LOCATION QUATION - Fadelan, Nahwani (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2017)
This Research is aimed to find out the economic sectors which are strongly and strategic to be developed as supporting economic growth at  Regency of Berau. Any analysis used in this research activity is alLocation Quotient analysis. The results of this research that are from 17 business  sectors, there are 10 sectors are maintain sectors of agricultural, forestry and fisheries sectors, mining sectors and expenses, water supply sector, waste management, waste and recycling, large and retail trade sector; accommodation and drinking repairs, real estate sectors, sector of education services, health sector services and social activities, and other services.